The Impact of Internal Communication, Awards, Organizational Culture, on the Performance of Employees in Production at Construction Company - Alfian Affandy Hadinata; Dewi Andriani (Indonesian Journal of Law and Economics Review, 2020)
This study aims to determine internal communication, awards and organizational culture of employee performance at PT. Wijaya Karya Beton Gempol Pasuruan. This research is a type of quantitative research with hypothesis testing. The sample used in this study were 63 employees at PT. Wijaya Karya Beton Gempol Pasuruan. The analytical tool used in this research is multiple linear regression analysis, determinant coefficient (R2), multiple correlation coefficient (R), f test, t test, and classic assumption test using SPSS version 18 for windows. Primary data in this study were obtained from questionnaires whose measurement used a Likert scale that was tested for validity and reliability. The results of this study prove that Internal Communication, Awards and Organizational Culture Against Employee Performance. effect simultaneously on employee performance. Internal communication has a partial effect on employee performance, awards have a partial effect on employee performance, organizational culture also has a partial effect on employee performance and for the variable that has the most significant effect on employee performance at PT. Wijaya Karya Beton Gempol Pasuruan is Organizational Culture.